A Hydroalcoholic Gel-Based Disinfection System for Deteriogenic Fungi on the Contemporary Mixed Media Artwork Poesia by Alessandro Kokocinski - Ambroselli, Francesca; Canini, Fabiana; Lanteri, Luca; Marconi, Martina; Mazzuca, Claudia; Pelosi, Claudia; Vinciguerra, Vittorio; Wicks, Elizabeth; Zucconi, Laura (Heritage, 2023)
The disinfection of deteriogenic microorganisms and the removal of induced chromatic alterations in artworks are still open challenges in the field of conservation. For this purpose, a new alcoholic hydrogel was tested to remove an extensive fungal attack from a multimaterial collage by the artist Alessandro Kokocinski and to mitigate chromatic changes caused by the contamination of its poster paper and plywood support layers. A Gellan gum-based hydrogel was used, which was modified by adding a high concentration of alcohol (66.7% ethanol), to give the system an effective disinfecting agent in addition to the detergent capacity of the gel for water-sensitive works of art. It was successfully tested on samples mimicking the complex stratigraphy of the artwork under study. To create replica mock-ups, the artwork materials and stratigraphy were investigated through diagnostic and laboratory techniques such as multispectral imaging, X-ray fluorescence spectroscopy, Fourier transform infrared spectroscopy, and pyrolysis coupled with gas-chromatography-mass spectrometry. The treatment was shown to have a disinfecting effect on the test samples and did not alter their structure, allowing us to apply the method to the artwork. Here, the hydrogel successfully removed and inhibited fungal proliferation in addition to mitigating the color changes caused by fungi.